Quantum Dots as Chemical Building Blocks: Elementary Theoretical Considerations - Remacle, Françoise; Levine, Raphael D. (Chemphyschem, 2001)
Quantum dots are clusters of atoms (or molecules) that are small enough that their electronic states are discrete. They can be prepared with a variety of compositions and covering ligands but are not quite identical. In particular, the dots will have a variable size. The study of the properties of individual dots is an active subject in its own right. Here we examine the electronic structure of assemblies of dots, where the dots are near enough that they interact. For the purpose of an elementary discussion, metallic dots are regarded as “atoms” with one valence orbital. The key point is that they are “designer” atoms because their electronic properties can be controlled through the synthetic method that is used to prepare the dots. Of direct concerns to us are the size of the dot and the nature of the ligands used to passivate the dots so that they do not coalesce. An important parameter is the energy cost, I, of adding an electron to a dot. The large size of the dots means that, unlike ordinary atoms, the Coulomb repulsion of the added electron is low. Other experimental control parameters are externally applied and include the ability to compress an assembly of dots, and thereby change the distance between them, or to subject them to static or alternating electromagnetic fields. The response to spectral probes for the electronic structure is discussed with special emphasis on new features, such as the onset of conjugation or the insulator‐to‐metallic transition, made accessible by the low charging energy of the dots. We propose a phase diagram of electronic isomers that can be accessed under realistic conditions. Quantum dots present the chemist with the opportunity to synthesize atomic‐like building blocks with made to measure electronic properties. The theorist is needed to describe the response of assemblies of such dots with special reference to the new and unique features which are made possible. These features include the not‐quite‐identical size of the dots, the different electronic isomers, the ability to switch between the isomers by mild external perturbations, and the fine tuning that can be achieved because of the low charging energy. The picture shows a schematic view of an STM, here as an asymmetric double junction, which probes the density of states of a quantum dot (either singly or in an array): By varying the tip voltage, it is possible to bring the Fermi level of the tip into resonance with the levels of the sample. The interplay between synthesis and theory makes possible the rational design of new electronic materials.